Coupling a Borehole Thermal Model and MT3DMS to Simulate Dynamic Ground Source Heat Pump Efficiency. Issue 2 (31st December 2021) - Zong, Yifei; Valocchi, Albert J.; Lin, Yu‐Feng F.
Abstract: We present a novel integrated two‐region model that couples simulation of local heat transfer processes in borehole heat exchangers (BHEs) with field‐scale heat transport simulation using MT3DMS to fulfill the dynamic simulation of the borehole geothermal systems. This includes the prediction of subsurface thermal perturbation induced by BHEs, derivation of the U‐pipe circulating fluid temperature profile within boreholes, and the evaluation of the ground source heat pump efficiency based on available time series of building heat load. In our approach, MT3DMS is the simulator for the two‐dimensional field‐scale heat transport, while new Python modules are developed to analytically solve the thermal transfer process within boreholes and interface iteratively with MT3DMS. A Python package for scripting MODFLOW‐based code named Flopy is used to establish the MT3DMS numerical model. The proposed model is validated against analytical solutions and we demonstrate the application to more complex test problems with field‐scale heterogeneity and pumping. Instructions are provided to access the source code and example problems which are available online. Abstract : Article impact statement : We developed an integrated "two‐region" model in Python to achieve the dynamic simulation of the borehole geothermal systems.